Pengaruh Brand Trust, Brand Equity, Brand Image dan Brand Ambassador terhadap Keputusan Pembelian Investasi Reksa Dana pada Aplikasi Bibit - Sulistyo, Rofan Dwi (Master of Management Diponegoro University, 2023)
One of the most popular digital investment is Bibit application, which offers an easy way to invest for beginners. The research was conducted by distributing questionnaires to 105 respondents. The data analysis technique uses multiple regression analysis with SPSS 25. It is concluded that Brand Trust and Brand Image partially have a significant effect, while Brand Equity and Brand Abassador partially have no significant effect on purchasing decisions. The simultaneous results show that all variables influence purchasing decisions, and the coefficient of determination